The Effect of Product Innovation and Product Quality on Competitive Advantage at Umkm One Florist Lampung - Tedi Ahmat Wijaya; Agus Purnomo (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to investigate the influence of product innovation as well as product quality for competitive advantage in One Florist MSMEs in Lampung. In the context of increasingly fierce business competition, product innovation as well as product quality are crucial factors when improving the competitiveness of MSMEs, especially in the florist industry. One Florist was chosen as the research subject due to its significant role in providing flower-based products with an innovative touch in the Lampung region. This study uses a quantitative method using owners and business actors at One Florist as respondents. Data was collected through a questionnaire covering aspects of product innovation, product quality, as well as perceptions of competitive advantage. Regression analysis was used to test the hypotheses and identify the extent to which product innovation as well as product quality contribute to competitive advantage. The result of this study is that product innovation is not significant for competitive advantage, but product quality has a significant effect on competitive advantage.